Fougerite: the not so simple progenitor of the first cells. Issue 6 (6th December 2019) - Duval, Simon; Baymann, Frauke; Schoepp-Cothenet, Barbara; Trolard, Fabienne; Bourrié, Guilhem; Grauby, Olivier; Branscomb, Elbert; Russell, Michael J.; Nitschke, Wolfgang
Abstract : We here review the extraordinary mineralogical properties of green rusts and their naturally occurring form, fougerite, and discuss the pertinence of these properties within the alkaline hydrothermal vent (AHV) hypothesis for life's emergence. We put forward an extended version of the AHV scenario which enhances the conformity between extant life and its earliest progenitor by extensively making use of fougerite's mechanistic and catalytic particularities.